Comparison of pedicle screw fixation by four different posterior approaches for the treatment of type A thoracolumbar fractures without neurologic injury - Zhu, Xu; Shao, Yijie; Lu, Yun; Sun, Jiajia; Chen, Jie (Frontiers in Surgery, 2023)
Abstract Purpose: This study was designed to compare the pedicle screw fixation by four different posterior approaches for the treatment of type A thoracolumbar fractures without neurologic injury. Methods: A total of 165 patients with type A thoracolumbar fractures without neurologic injury who received pedicle screw fixation by posterior approaches from February 2017 to August 2018 were enrolled in this study. They were further divided into the following four groups according to different posterior approaches: Open-C group (conventional open approach), Open-W group (Wiltse approach), MIS-F group (percutaneous approach with fluoroscopy guidance), and MIS-O group (percutaneous approach with O-arm navigation). The demographic data, clinical outcomes, and radiologic parameters were evaluated and compared among the four groups. Results: There were no significant differences in age, gender, fracture segment, and follow-up time. The incision length, blood loss, hospital stay time, and VAS (Visual Analog Scale) and ODI (Oswestry Disability Index) scores at the early stage of post-operation were the worst in the Open-C group. The MIS-O group showed significantly higher accuracy rate of pedicle position than other groups. The preoperative and postoperative AVH (anterior vertebral height) and VWA (vertebral wedge angle) obtain obvious correction in all patients immediately after and 1 year post-operation. No difference was found among the four groups at the final radiographic follow-up. Conclusions: The four different posterior approaches are effective in treating type A thoracolumbar fractures in our study. Each approach has its own individual strengths and weaknesses and therefore requires comprehensive consideration prior to use. Proper approaches selection is critical to patients.